A binary-medium-based constitutive model for porous rocks. (April 2023) - Chen, Yanbin; Liu, Enlong; Yu, Yanyang; Luo, Huiwu; Chen, Peishuai
Abstract: In this work, a binary-medium-based constitutive model for porous rocks is proposed under the framework of micromechanics. The porous rock at mesolevel is considered a two-phase composite composed of the matrix of the bonded medium and inclusions of the frictional medium. The bonded medium is defined by a Drucker–Prager solid phase where the pores are embedded, for which an upscaled model is introduced. Once the bonded medium breaks due to cracking, it transforms into the weakened frictional medium which is described by an elastic-perfectly plastic Mohr–Coulomb model. The breakage evolution is assumed to obey a Weibull-type function. The Mori–Tanaka method is extended to homogenize the mesoscopic binary-medium morphology. Numerical implementations of the binary-medium homogenization procedure and an implicit integration method for the bonded medium are conducted. Furthermore, the consistent tangent moduli in the local integration are also formulated. Finally, the indoor experimental investigations of Maldivian coral reef limestone (a type of porous rock) are presented, and the proposed model is applied to describe the macroscopic behavior of Maldivian coral reef limestone. The practicality of replacing the initial porosity in the proposed model with the P-wave velocity is verified as well.